The influence of customer perceived value and perceived service performance on customer satisfaction to malay upscale restaurants in Kuala Lumpur - Mohd Nazri Abdul Raji (Tanjong Malim, 2013)
The influence of customer perceived value and perceived service performance on customer satisfaction to malay upscale restaurants in Kuala Lumpur by Mohd Nazri Abdul Raji